2005
DOI: 10.1177/0883911505049896
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Polyurethane Coating on Vascular Stents for Enhanced X-ray Contrast

Abstract: A coating of polyurethaneurea was made from a solution on the surface of metal stents. The influence of cleaning, etching, chemical and ion beam modification (plasma immersion ion implantation) of the metal surface on the adhesion strength of the polyurethaneurea was analysed. Polyurethaneurea films imbedded with tantalum particles as a radiopaque filler maintained their strength and elasticity and produced clear X-ray contrast ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Ion‐beam implantation and PIII have been used for the modification of polyethylene, 13–21 polystyrene, 22–28 polytetrafluoroethylene, 29–34 poly(ethylene terephthalate), 35–38 poly(methyl methacrylate), 39–42 polyurethane, 43–47 and other polymers. Leading to increases in the hardness, electrical conductivity, and wettability, structural changes typical of ion‐irradiated polymers, such as carbonization, depolymerization, and oxidation, have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Ion‐beam implantation and PIII have been used for the modification of polyethylene, 13–21 polystyrene, 22–28 polytetrafluoroethylene, 29–34 poly(ethylene terephthalate), 35–38 poly(methyl methacrylate), 39–42 polyurethane, 43–47 and other polymers. Leading to increases in the hardness, electrical conductivity, and wettability, structural changes typical of ion‐irradiated polymers, such as carbonization, depolymerization, and oxidation, have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Ion-plasma treatment of materials is of great interest in many fields. For instance it is the treatment of polymers for the creation of implants and medical equipment [6][7][8]. Ionplasma treatment of the polymer leads to the formation of a special carbonized layer on its surface (Figure 1) which has essential properties for medical use [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising directions for improving its biocompatibility is ion-plasma surface treatment [3][4][5]. A carbonized layer with important for medical application properties is formed on the surface of the material as a result of treatment [6,7]. A protein, which acts as an intermediate link between the implant and the body and prevents rejection, inflammation of surrounding tissues and other unfavorable situations, can be planted on this layer [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lelah et al [2] reported that materials having higher surface soft segment concentration were more thromboresistant, and Hanson et al [3] reported that platelet consumption decreased as the percentage of surface carbon atoms forming hydrocarbon bonds increased. It was shown that, use of polyurethanes in the production of vascular stents or coatings of the stents with polyurethanes increase the biological acceptance of the stents [4][5][6][7]. Further modifications of polyurethanes with ATH complex [8] or with zwitterionic sulfobetaine monomer [9] increase their acceptance in stent applications.…”
Section: Introductionmentioning
confidence: 99%